Pit-Stop Power Generator - Mat Zian @ Mat Zin, Ahmad Faiz (Multidisciplinary Applied Research and Innovation, 2023)
A pit-stop power generator is a ramp that produces electricity using piezo plates. Hydroelectric dams, solar panels, and nuclear power are all common sources of electricity. The objectives of the project are to design the pit-stop generator that work, to create an alternate way to supply power inside tool booth and to use a renewable source of electricity. Our purpose is to provide low-cost electricity [1]. If this idea is put into action, it will be possible to make changes to supply power to remote areas. People can carry on with their daily tasks without difficulty in this manner. The creation and testing of a pit-stop power generator is presented in this project, which attempts to give an alternate method of producing electricity. The goals are to design and build a working Pit Stop Power Generator. Aside from that, the plan is to provide a backup power source for the toll booth. The mission of the undertaking. The project works on the premise of transforming mechanical force into electrical energy. Our goal is to develop an alternative energy source. This project development process includes machine design using SolidWorks, material selection, metal works fabrication, which includes machining, cutting assembly, testing, and re-modification, to generate a fully working project. Three different elements that influence the current produced are tested to enhance the output voltage. The prototype was designed using using the result and considering the facts of strength and toughness. 11.1 volts is the maximum current that can be collected. The LED lamp inside the toll booth will receive this current.